LEGAL PROTECTION OF INTELECTUAL PROPERTY RIGHTS IN INDICATION GEOGRAPHICS IN INDONESIA - Oxtalevanus Siallagan; Mas Rahma (Universitas Airlangga, 2023)
Indonesia is a country that is rich in natural resources, the wealth of natural resources provides various kinds of extraordinary natural gift potentials so that from these potentials produce results of vegetable and biological cultivation that characterize the geography where the potential is located. In this study, the authors used a normative-applied approach. Data collection in writing this research is done by means of document studies, namely studying legal materials in the form of primary legal materials, secondary legal materials and tertiary legal materials. Based on the results of the research, it can be seen that: (1) Protection of geographical indications cannot be separated from the joint ef orts of interested parties in the region to be involved in the initial process (during the inventory of potential regional goods/products). This agreement is a reflection of the results of joint work to seek an advantage among fellow producers in accordance with the characteristics of the area where the producer lives. (2) Legal ef orts that can be taken by the government to encourage the growth of protection of geographical indications are that the government establishes a law on geographical indications.